Accelerator Mass Spectrometry (AMS) in Radioecology. (June 2018) - García-León, M.
Abstract: Accelerator Mass Spectrometry (AMS) provides with an excellent sensitivity for the determination of radionuclides in the environment. In fact, conventional radiometric techniques can hardly compete with AMS in the solution of many problems involving the measurement of very low levels of radioactivity in Nature. For that reason, during the last years AMS has become a powerful tool for Radioecology studies. In this paper a review is done on the evolution of AMS applications to the measurement of environmental radioactivity and, therefore, its contribution to the understanding of radionuclide behavior in Nature. For that, the advantages of using AMS to determine key nuclides as 129 I, 14 C, Pu-isotopes and others in different natural compartments will be discussed. The content of the paper is illustrated with the contributions to these studies of the Spanish National Center for Accelerators (CNA) AMS systems. Highlights: Accelerator Mass Spectrometry (AMS) is described as a powerful analytical tool. The applications of AMS to measurements of radioactivity in the environment are reviewed. Measurements of 14 C, 129 I, Pu-isotopes, 236 U and other radionuclides by AMS are studied.